Contestation of Religious Discourse Among Muslim Dawah Activists in Contemporary Indonesia - Achmad Muhlis; Abd Hannan (Islam Transformatif : Journal of Islamic Studies, 2023)
This study examines the phenomenon of religious contestation among Muslim preachers in contemporary Indonesia. This study is a qualitative research and uses the digital ethnography (netnography) approach. This study uses two sources of data, namely, primary data, in the form of text, visuals, videos, and images obtained from several social media platforms, and secondary data in the form of literature data from previous studies. This study finds that the contestation of religious discourse among Muslim preachers in Indonesia, in particular that which have taken place on social media, has revolved around four major issues, namely, the controversies of â€œrendang babiâ€ (pork rendang), â€œpawang hujanâ€ (the rain shaman), the regulation of sound amplifiers in mosques and prayer spaces, and the art of wayang (puppetry). The religious contestation among Muslim preachers in Indonesia follows two patterns. The first is the substantive-inclusive religious narrative pattern, which emphasizes the core and principles of a problem. Next is the exclusive legal-formalist narrative, which tends to be normative and rigid. This last narrative is typically associated with Muslims preachers who have conservative views.Â Keyword : Religious contestation, social media, religious figure, Muslim preacher.Â Studi ini bertujuan melakukan kajian terhadap media sosial dan fenomena kontestasi keagamaan di kalangan pendakwah Muslim di Indonesia kontemporer. Kajian ini merupakan penelitian kualitatif dengan menggunakan pendekatan etnografi digital (netnografi). Sumber data penelitian ini ada dua, data primer berupa teks, visual, video, dan gambar yang diperoleh dari sejumlah media sosial, serta data sekunderÂ berupa data-data kepustakaan yang didapat dari hasil kajian sebelumnya. Berdasarkan analisa data lapangan, studi ini mendapati temuan bahwa kontestasi wacana keagamaan antarpendakwah muslim di Indonesia yang selama ini berlangsung di kanal media sosial, itu tergambar dalam empat isu besar, yakni isu rendang babi, pawang hujan, aturan terkait pengeras suara di masjid dan musala, dan terakhir adalah isu tentang seni wayang. Berdasarkan narasinya, kontestasi keagamaan di kalangan pendakwah Muslim di Indonesia memiliki dua pola, yakni narasi agama berpola subtantif-inklusif, lebih menekankan pada isi, inti, dan pokok suatu permasalahan. Berikutnya, yaitu eksklusif-legal formalis, narasi keagaman yang cenderung normatif dan kaku. Bentuk narasi ini lazimnya identik dengan aktor agama atau pendakwah muslim beraliran paham konservatif..Kata Kunci : Kontestasi Agama, Media Sosial, Aktor agama, Pendakwah Muslim.